‘Larks in Season’: The Comic Almanack (1835–54) - Brian Maidment (Cahiers Victoriens et Edouardiens)
By the 1830s, the almanac was one of few print genres to have found a broad readership across all classes of society. Differing kinds of almanacs provided either general information linked to the agricultural, ecclesiastical, or parliamentary year or else spectacularly inventive predictions. Early-Victorian print culture attempted to stamp out superstitious predictive almanacs and establish the genre as an authoritative source of information. One response to such reformist impulses was the comic or travesty almanac, and this essay centrally forms a study of the longest lasting and most successful satirical almanac, The Comic Almanack, which ran from 1835 until 1854. With a list of contributors that included Thackeray, Horace Mayhew, and Gilbert à Beckett and centrally dependent on both etched and wood engraved illustrations by George Cruikshank and H. G. Hine, The Comic Almanack both parodied and celebrated the almanac tradition. In particular, it showed a sustained interest in the visual potential of the graphic and typographical patterning of the almanac form. The Comic Almanack formed one of several travesty almanacs that enlivened print culture in the 1830s and that fostered a wide variety of early-Victorian parodies of supposedly authoritative and informative print genres.